Pre-conception status, obstetric outcome and use of medications during pregnancy of systemic lupus erythematosus (SLE), rheumatoid arthritis (RA) and inflammatory bowel disease (IBD) in Japan: Multi-center retrospective descriptive study. Issue 5 (2nd September 2020) - Tsuda, Sayaka; Sameshima, Azusa; Sekine, Michikazu; Kawaguchi, Haruna; Fujita, Daisuke; Makino, Shintaro; Morinobu, Akio; Murakawa, Yohko; Matsui, Kiyoshi; Sugiyama, Takao; Watanabe, Mamoru; Suzuki, Yasuo; et al.
Abstract: Objective: To describe the pre-conception status, pregnancy outcomes, and medication prevalence in systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), Crohn's disease (CD), and ulcerative colitis (UC). Methods: E-mail-based questionnaire survey for the Japan Maternal Fetal Intensive Care Unit Network hospitals inquiring prevalence and clinical features of SLE, RA, CD and UC complicated pregnancies for 2 years. Results: The number of SLE, RA, CD and UC among 69, 810 deliveries was 184, 139, 27 and 178, respectively. Less than half of pregnancies were planned. Assisted reproductive technology (ART) pregnancy rates were higher in SLE, RA and UC than in the general population (11.4, 23.0 and 7.4 vs 5.1%, p  < .001 each). Preterm delivery, preeclampsia, and fetal growth restriction (FGR) were more frequent in SLE than in the general population (39.4 vs. 5.6% p  < .001, 15.0 vs. 6.0% p  < .001, 12.9 vs 4.2% p  < .001). Prevalence of preterm delivery in RA and UC (27.5 vs. 5.6% p  < .001, 11.3 vs. 5.6% p  < .05) and FGR in CD (28.6 vs. 4.2% p  < .001) was also higher than that in the general population. Conclusion: SLE, RA, CD, and UC complicated pregnancies were at high risks of obstetric adverse outcome. High ART rates necessitate pre-conception counseling in SLE, RA, and UC pregnancies.